ANALISIS PROSEDUR PENGELOLAANARSIP DINAMIS AKTIF DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PESISIR SELATAN - Mega Zalma; Armida Silvia; Menik Kurnia Siwi (Jurnal Ecogen, 2018)
The purpose of this research is to know the active dynamic archives management procedure, in the Department of Population and Civil Registry of the South Coast. This method of this research is descriptive qualitative method, the source data of this research determined by purposive sampling. Validity test of data used Triangulation Technique. The result of this research showed that creation, management, re-invention and archive storage space not compatible with SOP. This happens because there is no archivist or special officer performing archive management and filing facility still not adequate. Based on the research the author give some suggestion for the employers and the leaders of Departement of Population and Civil Registry of the South Coast can give more attention and providing archive storage space equipped. Keyword: Analysis, Management, Active Dynamic Archives